2015
DOI: 10.1021/acs.macromol.5b01090
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Nickel(II) Phenoxyiminato Catalysts: Exploring the Role of Fluorine Atoms in Controlling Polyethylene Productivities and Microstructures

Abstract: A series of neutrally charged Ni(II) phenoxyiminato catalysts with fluorine atoms at different positions on the N-terphenyl motif are synthesized, and their abilities to polymerize ethylene are compared. At 25°C, the orthofluorinated Ni-5F, Ni-3F′, and Ni-2F achieve significantly higher polymerization activities than Ni-3F and Ni-0F. In addition, branch density and molecular weight of the obtained polyethylenes vary gradually in the order of Ni-5F, Ni-3F, Ni-3F′, Ni-2F, and Ni-0F. Based on the X-ray crystal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 60 publications
5
34
0
Order By: Relevance
“…This finding suggested that the ortho-F substitution suppressed chain-walking and favored β-H elimination. The explanation for this observation is uncertain but may be due to weak hydrogen bonding between the ortho-fluorine atoms and the coordinated ethylene during the insertion transition state; similar results have been observed elsewhere [39][40][41]. This lower branching content of the polyethylene formed by Ni4 was also consistent with the higher Tm of the polymer.…”
Section: Microstructural Analysis Of the Polyethylenessupporting
confidence: 77%
“…This finding suggested that the ortho-F substitution suppressed chain-walking and favored β-H elimination. The explanation for this observation is uncertain but may be due to weak hydrogen bonding between the ortho-fluorine atoms and the coordinated ethylene during the insertion transition state; similar results have been observed elsewhere [39][40][41]. This lower branching content of the polyethylene formed by Ni4 was also consistent with the higher Tm of the polymer.…”
Section: Microstructural Analysis Of the Polyethylenessupporting
confidence: 77%
“…Note that bond length of Ni(1)−O(2) and Ni(1)−O(3) in 3 b is 3.817 and 4.436 Å, respectively, either is longer than the sum of the van der Waals radii of nickel and oxygen (3.15 Å) . In addition, bond length of Ni(1)−F(1) and Ni(1)−F(2) in 3 h is 3.791 and 4.487 Å, respectively, while the sum of van der Waals radii between Ni and F atom is 3.31 Å . This result reveals that the interaction between −F or −OMe group and the nickel center for both 3 b and 3 h is negligible.…”
Section: Resultsmentioning
confidence: 98%
“…Fluorine substituents in these catalysts is also effective in tuning elementary reaction pathways, likewise. Phenoxy‐imine nickel catalysts bearing fluorine (F) substituents or fluorocarbon (C n F 2n+1 ) substituents have been thoroughly studied in ethylene polymerization (Scheme 1B) [67–74] . The effect of fluorine substituents on thermal stability and activity of catalyst, and molecular weight and branching density of polymer is observed.…”
Section: Introductionmentioning
confidence: 99%